PENERAPAN ANALISIS REGRESI LINIER BERGANDA UNTUK MENENTUKAN PENGARUH PELAYANAN PENDIDIKAN TERHADAP EFEKTIFITAS BELAJAR TARUNA DI AKADEMI MARITIM YOGYAKARTA - Ningrum Astriawati (Majalah Ilmiah Bahari Jogja, 2016)
Multiples linear regression analysis is used to review examines the relationship of two or more between independent with dependent variable. This research aims to know how to influence education services (as independent variable) with the cadets learning effectiveness (as dependent variable), reviewed from the performance of lecturers, administration services, program studies management and infrastructure which is owned by the Maritime Academy in Yogyakarta. This research approach using Ordinary Least Squares (OLS). The relationship between four independent variables to the dependent variable with strong relationship were program study management and performance of lecturers. The program studies management and boarding costs lecturers good so learning effectiveness cadets also getting good.